Full-Wave Analysis Of Air-Filled Substrate Integrated Waveguide - Zubir, Ahmad Ikhwan Mohd (Universiti Sains Malaysia, 2021)
The air-filled substrate integrated waveguide (AFSIW) is a new type of transmission line that has been used as an interconnect with traditional SIW circuits to lower circuit losses. To achieve effective connectivity in SIW, various approaches for the transition between air-filled and dielectric-filled mediums have been made. The insertion and return losses along the transition must be minimized to improve the transition's performance. The transitional losses, on the other hand, are incompletely understood. This is because electromagnetic wave propagation through inhomogeneous media with variable geometry is difficult to quantify in terms of losses. This thesis presents the losses in the transition using full-wave analysis in Ka-band frequency which is from 26 to 40 GHz by using software ANSYS HFSS. After the study has been done, the simulation shows that reflection losses that have been obtained are from 24.17 to 36.32 GHz while the transmission losses are from 14.32 to 17.46 GHz at Ka-band frequency. The findings of this research will aid in the invention of more compact coplanar circuit designs for any frequency band with improved performance.